Shifting to hydrological/hydrographic boundaries: a comparative assessment of national policy implementation in the Zerafshan and Ferghana Valleys - Wegerich, Kai (Informa UK Limited, 2015)
In the literature on the implementation of national policies there is an assumption that these get implemented uniformly within one country. Here, with a focus on the implementation of national policy on shifting from administrative to hydrological/ hydrographic principles of water management in the Zerafshan Valley and the Ferghana Valley in Uzbekistan, this assumption is questioned. The case study demonstrates that national policies are resisted by lower-level bureaucrats, leading to diverse, even contradictory, outcomes of the same policy. The vested interests of a multiplicity of bureaucracies, the power of individual bureaucrats, and the discretional power given to bureaucracies in interpreting national policy are responsible for the different outcomes. The article calls for more comparative assessments across different regions for a better understanding of policy implementation.